THE INFLUENCE OF CELEBRITY CONGRUENCE ON PURCHASING DECISIONS WITH BRAND QUALITY AS A MODERATING VARIABLE - Syahrial Sidik; Alya Elita Sjioen; Rudi Kurniawan; Abdul Latif; Abdul Razak Munir (JURNAL ILMIAH EDUNOMIKA, 2024)
This research is quantitative research with an exploratory approach, namely using a number of studies related to Celebrity Congruence, Pruchase Decision, and Brand Quality as the main reference and basic material to create novelty in the research carried out. This research uses primary data obtained from sellers of kebuli rice as many as 150 MSMEs and 150 consumers who have purchased kebuli rice. This data can be categorized as primary data because it was obtained directly. The instrument for obtaining this data uses an online questionnaire which contains 5 statements, namely strongly agree, agree, normal/so-so statement, disagree and strongly disagree which are used as validity test material. The data in this study was analyzed using the smart PLS 4.0 analysis tool. The result in this research show that the researcher's first hypothesis regarding the Celebrity Conguruence variable can have a positive relationship direction and a significant influence on Purchasing Decisions can be proven and accepted because the P-Values value is below the 0.05 significance level, namely 0.011. This is due to the promotional influence of Sleebriti which has the main tasks of knowledge, skills, markets and so on which are in line with the products being marketed which can significantly influence purchasing decisions However, this research shows more significant results than previous research. Apart from that, in the second row of the third table the path coefficients show similar results if the Brand Quality variable can strengthen the influence of the Celebrity Congurence variable on Purchasing Decisions because the P-Values value is below the 0.05 significance level, namely 0.000, which is more significant than the direct test of 0.001. This is because Brand Quality is the most important thing to maintain and become the attention of buyers after seeing promotions from Celebrity Congruence. Based on this, the first and second hypotheses in this study are correct and can be proven. Keywords: Celebrity Congruence, Purchasing Decisions, Brand Quality